Enhancing ideal personal qualities of counselor candidates: Empowering through digital module and peer modelling - Indreswari, Henny; Apriani, Rizka; Utami, Nugraheni Warih; Atmoko, Adi; Pamintarso, Kheren Carollina (International Journal of Research in Counseling and Education, 2022)
Universities aim to achieve intelligent education through innovative learning methods. Students desire models to develop their skills, and this can be achieved through peer modelling with their peers. This research aims to develop a peer modelling-based digital module to enhance students' understanding of the Personality Development Practicum course, as an effort to improve the ideal personal qualities of prospective counselors. The research design uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects in this study are material experts (guidance and counseling lecturers), media experts (learning technology lecturers), and potential users (guidance and counseling students). The results show that the digital module is equipped with video explanations, PowerPoint, infographics, motion graphics, and peer modelling videos. Based on the validation results by material experts, media experts, and potential users, the digital module is considered valid in terms of accuracy, usefulness, attractiveness, and ease of use. Further empirical evidence is needed to support the use of the peer modelling-based digital module in developing the ideal personal qualities of prospective counselors.